Degradation of reactive black 5 from textile SME wastewater by using fenton-like oxidation - Leong, Yong You (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Textile SME is the largest sector in the SMEs Malaysia. It has high consumption of water following discharge large amount of wastewater with high load of contaminants. The dyes released to the environment from textile industry during dyeing processes cause water pollution. In this study, batik SME wastewater was selected and the characteristics of batik SME wastewater were studied. Besides that, this study was investigated the efficiency of degradation of Reactive Black 5 from batik SME wastewater by using Fenton-like oxidation. Three parameters were concerned in this study, which were dosage of Fe3+, dosage of H2O2 and reaction time. An experimental design was used to evaluate the individual and interactive effect of parameters depended on five-level Central Composite Design. Response Surface Methodology was used to determine the optimization of these parameters on treatment on the percentage efficiency of Reactive Black 5 removal. The optimized condition from this study were shown as Fe3+ dosage = 4.98 mM, H2O2 dosage = 94.55 mM and reaction time = 62.84 min. Under this condition, maximum percentage of Reactive Black 5 removal was achieved 91% which fitted-well to the model prediction. Therefore, Fenton-like oxidation process is effective for the treatment of batik SME wastewater.